(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article thoroughly examines the theoretical and practical advantages of applying a risk-based audit approach in organizing audit activities in accordance with International Standards on Auditing (ISA). Risk-based auditing enables auditors to focus more heavily on areas with a high likelihood of material misstatements in financial statements, make efficient use of audit resources, and conduct a deeper assessment of internal control systems. The study scientifically highlights the impact of this approach on information transparency, corporate governance efficiency, investor trust, and audit quality within joint-stock companies.